VCAM-1 targeted alpha-particle therapy for early brain metastases. Issue 3 (20th September 2019) - Corroyer-Dulmont, Aurélien; Valable, Samuel; Falzone, Nadia; Frelin-Labalme, Anne-Marie; Tietz, Ole; Toutain, Jérôme; Soto, Manuel Sarmiento; Divoux, Didier; Chazalviel, Laurent; Pérès, Elodie A; Sibson, Nicola R; Vallis, Katherine A; et al.
Abstract: Background: Brain metastases (BM) develop frequently in patients with breast cancer. Despite the use of external beam radiotherapy (EBRT), the average overall survival is short (6 months from diagnosis). The therapeutic challenge is to deliver molecularly targeted therapy at an early stage when relatively few metastatic tumor cells have invaded the brain. Vascular cell adhesion molecule 1 (VCAM-1), overexpressed by nearby endothelial cells during the early stages of BM development, is a promising target. The aim of this study was to investigate the therapeutic value of targeted alpha-particle radiotherapy, combining lead-212 ( 212 Pb) with an anti–VCAM-1 antibody ( 212 Pb-αVCAM-1). Methods: Human breast carcinoma cells that metastasize to the brain, MDA-231-Br-GFP, were injected into the left cardiac ventricle of nude mice. Twenty-one days after injection, 212 Pb-αVCAM-1 uptake in early BM was determined in a biodistribution study and systemic/brain toxicity was evaluated. Therapeutic efficacy was assessed using MR imaging and histology. Overall survival after 212 Pb-αVCAM-1 treatment was compared with that observed after standard EBRT. Results: 212 Pb-αVCAM-1 was taken up into early BM with a tumor/healthy brain dose deposition ratio of 6 (5.52e10 8 and 0.92e10 8 ) disintegrations per gram of BM and healthy tissue, respectively. MRI analyses showed a statistically significant reduction in metastatic burden after 212 Pb-αVCAM-1 treatment compared with EBRT ( P < 0.001), translating to an increase in overall survival of 29% at 40 days post prescription ( P < 0.01). No major toxicity was observed. Conclusions: The present investigation demonstrates that 212 Pb-αVCAM-1 specifically accumulates at sites of early BM causing tumor growth inhibition.